3D printing using metakaolin-based geopolymers - challenges - Gonçalves, C. E.C. [UNESP]; Ribeiro, T. M. [UNESP]; Santos, S. F. [UNESP] (FapUNIFESP (SciELO), 2023)
Alternative cementitious materials able to partially replace or supplement the use of Portland cement, such as geopolymers, are becoming increasingly attractive due to lower emissions of air pollutants during their production. In addition, coupling geopolymers with additive manufacturing technologies such as 3D printing can contribute to achieving some of the Sustainable Development Goals (SDG) of settling housing issues. Additive manufacturing allows producing pre-fabricated building elements or even entire houses. However, enabling 3D printing using geopolymers requires understanding concepts of rheology, technology, and material sciences, such as different possibilities of formulations, rheological behavior, printing parameters, curing methods, reinforcement content, and fiber type. Cylindrical specimens were printed both with and without polypropylene fibers by controlling the geopolymer matrix formulation, printer displacement speed, mass percentage of fibers, and material flow through the printer's extruder nozzle.
Keywords: 3D printer; additive manufacturing; geopolymerization; polypropylene fibers; rheology